SISTEM INFORMASI PELAYANAN KESEHATAN DI LABORATORIUM KLINIK PARANIDA BANDUNG - Permatasari, Deasy; Wijaya, Fanji (PETIR, 2018)
Clinical Laboratory Paranida a means of supporting health. Improving the Quality of Laboratory Services through standardization of services that includes aspects of service procedures, inspection procedures and diagnostic accuracy you need for a healthier life. Found problems that occur in the processing of patient data, which is still done with the recording system and the calculation process payment transactions are still not maximizing the computerized system so well that in making patient data reports and financial statements requires quite a long time. The method used is the system approach structured design. Where structured design is the development of a model of problem solving analysis results by using acomputer system that has components - components and relationships are the same or similar to the original problem. The development of the system used in this research is to create a prototype using an iterative method in the model System Development Life Cycle (SDLC). The tool used to describe the system model is a data flow diagram (FlowMap), context diagrams, and data flow diagram (DFD), as well as in database design using a data dictionary, normalization, and Entity Relation Diagram (ERD). In the design of Health Care Information Systems is using the programming language supported by NetBeans IDE 6.9.1 with MySQL as the database. After passing through the stages of implementation and testing, the results obtained are better data storage and ease of administration are effective in preparing reports and archiving structured reports. System information created is expected to assist the Clinical Laboratory Paranida in improving health services and their performance.